KEBIJAKAN POLSEK TANDES SURABAYA BAGI KEHARMONISAN RUMAH TANGGA TAHANAN PERSPEKTIF MASLAHAH MURSALAH - Mirza Aziz Didik Putra (State Islamic University (UIN) of Sunan Ampel, 2017)
This is a field research that aims to find out the policies of the district police of Tandes, Surabaya for the harmony of household prisoners and the analysis of maslahah mursalah on those policies. The result of the research concludes that the policies of the district police of Tandes, Surabaya allow prisoners to meet their families on terms that have been agreed by prisoners and police officers of Tandes, Surabaya. It is an effort to develop cases that are being experienced by prisoners as well as stabilizing emotional condition of the prisoners who have already married. Such policies are in line with maqasid al-shariah and maslahah mursalah concept. All that can be seen from the fulfillment of the five basic guarantees of life (salvation of religion, soul, mind, descendant, and possession) and fulfilled the conditions that exist in maslahah mursalah. It’s just that the government’s attention to the rights and obligations of prisoners who have already married is felt to be lack. Therefore, the government should pay more attention to the rights of the people in making policy. For the people, they should pay attention to the fate of their families who become prisoners, not to be ostracized because it is not impossible they want to be better than ever.